2015
DOI: 10.1111/bjet.12361
|View full text |Cite
|
Sign up to set email alerts
|

Understanding university faculty perceptions about innovation in teaching and technology

Abstract: The purpose of this research is to understand faculty perceptions about innovation in teaching and technology in a college of education in a research‐intensive university. This study was motivated by the creation of a new initiative begun in a large college of education at a Carnegie Research‐Intensive university to promote innovation in teaching with the support and creative use of technology. This study used Q methodology, a mixed methods research design involving quantitative and qualitative analysis of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 26 publications
1
28
0
2
Order By: Relevance
“…For example, university administrators may view technology as a tool to attract and retain students, whereas faculty may struggle to determine how technology coincides with existing pedagogy (Lawrence & Lentle-Keenan, 2013;Lin, Singer, & Ha, 2010). In addition, some faculty may be hesitant to use technology due to lack of technical knowledge and/or skepticism about the efficacy of technology to improve student learning outcomes (Ashrafzadeh & Sayadian, 2015;Buchanan, Sainter, & Saunders, 2013;Hauptman, 2015;Johnson, 2013;Kidd, Davis, & Larke, 2016;Kopcha, Rieber, & Walker, 2016;Lawrence & Lentle-Keenan, 2013;Lewis, Fretwell, Ryan, & Parham, 2013;Reid, 2014). Organizational barriers to technology adoption are particularly problematic given the growing demands and perceived benefits among students about using technology to learn (Amirault, 2012;Cassidy et al, 2014;Gikas & Grant, 2013;Paul & Cochran, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, university administrators may view technology as a tool to attract and retain students, whereas faculty may struggle to determine how technology coincides with existing pedagogy (Lawrence & Lentle-Keenan, 2013;Lin, Singer, & Ha, 2010). In addition, some faculty may be hesitant to use technology due to lack of technical knowledge and/or skepticism about the efficacy of technology to improve student learning outcomes (Ashrafzadeh & Sayadian, 2015;Buchanan, Sainter, & Saunders, 2013;Hauptman, 2015;Johnson, 2013;Kidd, Davis, & Larke, 2016;Kopcha, Rieber, & Walker, 2016;Lawrence & Lentle-Keenan, 2013;Lewis, Fretwell, Ryan, & Parham, 2013;Reid, 2014). Organizational barriers to technology adoption are particularly problematic given the growing demands and perceived benefits among students about using technology to learn (Amirault, 2012;Cassidy et al, 2014;Gikas & Grant, 2013;Paul & Cochran, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it is critical to note that innovation is deeply interrelated with the concept of competence. To ensure training in an innovative way, modern teachers need the competences to "adapt to rapidly changing and ever-increasing technology innovations for teaching" (Kopcha, Rieber, & Walker, 2015). Among these generic (or key) competences, there is autonomy (Key Competences, 2007), that is reported as "the competence to develop as a self -determined, socially responsible and critically aware participant in (and beyond) educational environments, within a vision of education as (inter)personal empowerment and social transformation" (Jiménez Raya, 2007, 33).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The review of the literature demonstrated that the idea of association between teachers' innovative work behavior and their autonomy is directly or indirectly expressed in a number of works (Chang et al, 2011;Gorozidis, & Papaioannou, 2014;Kopcha, Rieber, Walker, 2015;Marchenko, 2013;McGinity, 2015). But the details and possible implications of this idea under the current educational circumstances are still understudied.…”
Section: Introductionmentioning
confidence: 99%
“…This can be caused by the fact that modern university teachers are involved in a plenty of activities that include teaching, learning new information and developing new skills, keeping abreast of technological innovations, dealing with students, parents, and the community and ongoing adaptation to the measurement systems. Teaching staff nowadays also needs the competences to "adapt to rapidly changing and ever-increasing technology innovations for teaching" (Kopcha, Rieber, & Walker, 2015) and constantly innovate.…”
Section: Relevancementioning
confidence: 99%